75 years ago: discovery of resin adhesion to acid-etched enamel - a comparison of the 1949 and 1955 methods - Staehle, Hans Jörg; Sekundo, Caroline (The journal of adhesive dentistry, 2024)
Purpose: This paper describes previously unknown details about the discovery of resin adhesion to acid -etched human enamel. Materials and Methods: A literature review was performed through manual assessments. Primary sources revealing the discovery of resin curing on etched enamel were analyzed considering the research objectives and methodological procedure during that era, including the type of teeth used, preparatory measures, acid -etching process, type of resin and its application, and follow-up observations. Additionally, the political and economic contexts were examined. Results: In 1949, acid etching was found to promote adhesion with acrylic resin, a finding described again in 1955. The 1949 studies utilized nitric acid for enamel etching and the acrylate resin Paladon from the Kulzer company (Germany). Conversely, the 1955 investigations employed phosphoric acid and an unnamed acrylate, likely a self -curing resin supported by Kulzer in the late 1930s. Disparities in the 1949 and 1955 findings can be ascribed to varying objectives and test conditions amidst a turbulent political backdrop, significantly impacting the Kulzer company. Conclusion: The discovery of resin adhesion to acid -etched enamel, approaching its 75th anniversary in 2024, is a landmark in 20th -century adhesive dentistry. Paladon represents a pioneering compound, exemplifying the influence of political, ideological, and economic factors on scientific advancements during that period.